Is enteral nutrition a primary therapy in cancer patients? - Bozzetti, F (1994)
At present, there is limited evidence for the role of enteral nutrition as a primary therapy in cancer patients. Cachexia commonly occurs in patients with advanced cancer. A consensus view from a large number of studies suggests that cachexia cannot be fully reversed by vigorous enteral nutritional support. A review is included of the available data on the effects of enteral nutritional support on the common indices of nutritional state and on the final outcome of patients receiving enteral nutrition in conjunction with radiotherapy or chemotherapy, or both. The 'nutritional' effects are probably limited because the duration of the nutritional support in most studies consists of a few weeks while malnutrition in the cancer patients often occurs over many months.